Expression of IGF-1R in oral submucous fibrosis and oral squamous cell carcinoma – An RT-PCR study - Vivek Nayyar; Vinay Hazarey; Sindhu M. Ganvir; Hemant J. Purohit; Reshma Talkal; Kiran Jot (Oral Oncology Reports)
Objectives: With the rising number of cases of oral submucous fibrosis (OSMF) undergoing malignant transformation into oral squamous cell carcinoma (OSCC), it is needed to detect the changes at the earliest. Several molecular markers have been used for this purpose, and insulin-like growth factor receptor 1 (IGF-1R) is one of the markers in vogue for several human malignancies. Thus, we compared the expression of IGF-1R mRNA in normal oral mucosa (NOM), OSMF, and OSCC. Materials and methods: Thirty biopsy tissue samples for each of the three groups, NOM, OSMF, and OSCC, were taken and analyzed histopathologically and then subjected to RT-PCR for evaluation of the expression of IGF-1R mRNA in each of them. Results: There was an upregulation of IGF-1R mRNA in OSMF tissue samples as compared to NOM, but a downregulation as compared to OSCC. There was a 3.24-fold upregulation of IGF-1R mRNA expression in OSMF as compared to NOM and a 1.31-fold downregulation as compared to OSCC. Likewise, there was a 4.2-fold upregulation of IGF-1R mRNA expression in OSCC as compared to NOM and 1.31-fold upregulation as compared to OSMF. Moreover, the expression was more in OSMF patients with interincisal opening (IIO) < 27 mm as compared to those with IIO >27 mm and also was found to increase with the grade of OSCC. Conclusion: The study reflected a potential role of IGF-1R in the pathogenesis of OSMF and OSCC, thus implying its possible exploitation as a diagnostic and prognostic marker and also as a therapeutic target in future.